2018
DOI: 10.1103/physrevb.97.060402
|View full text |Cite
|
Sign up to set email alerts
|

Origin of temperature and field dependence of magnetic skyrmion size in ultrathin nanodots

Abstract: PACS:Understanding the physical properties of magnetic skyrmions is important for fundamental research with the aim to develop new spintronic device paradigms where both logic and memory can be integrated at the same level. Here, we show a universal model based on the micromagnetic formalism that can be used to study skyrmion stability as a function of magnetic field and temperature. We consider ultrathin, circular ferromagnetic magnetic dots. Our results show that magnetic skyrmions with a small radius-compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 48 publications
1
90
0
Order By: Relevance
“…Our comprehensive investigation of confined Néel skyrmions offers a firm foundation tailor-made for such efforts. Second, the manifestly distinct trends in skyrmion configuration and size with variation of κ go beyond existing predictions [5,24,27,28]. While recent studies have incorporated the effects of granularity [32,41], interlayer coupling [6], and dipolar interactions [28,37], we posit that future studies of confined skyrmions would benefit from harnessing their differing behavior with thermodynamic stability.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our comprehensive investigation of confined Néel skyrmions offers a firm foundation tailor-made for such efforts. Second, the manifestly distinct trends in skyrmion configuration and size with variation of κ go beyond existing predictions [5,24,27,28]. While recent studies have incorporated the effects of granularity [32,41], interlayer coupling [6], and dipolar interactions [28,37], we posit that future studies of confined skyrmions would benefit from harnessing their differing behavior with thermodynamic stability.…”
Section: Discussionmentioning
confidence: 72%
“…6(b)] and H [ Fig. 6(c)] in the context of extensive predictions of these trends [5,6,24,27,28,37]. Figure 6(b) shows that the normalized size, d m sk /w, reduces monotonically with increasing D/A, with a sharp jump at κ ∼ 1.…”
Section: Variation Of Skyrmion Sizementioning
confidence: 89%
See 1 more Smart Citation
“…, to the spin current that exerts spin-torques on the skyrmion, G is the Gilbert damping. The skyrmions experience a velocity component, , towards the edge of the wire 9,18,19 . The skyrmion Hall angle is then given by tan Sky = − / G .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental transport measurements based on such mechanisms showed that high current densities on the order of 10 12 A m −2 are required to achieve practical speeds of about 100 m s −1 [12,13]. The elevated temperatures at such high current densities can drastically reduce the propagation speed of skyrmions while the risk of skyrmion annihilation increases significantly [14][15][16].…”
Section: Introductionmentioning
confidence: 99%